2016
DOI: 10.1155/2016/2787623
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Antimicrobial Ability and Cytotoxicity on Two Melanoma Cell Lines of a Benzylamide Derivative of Maslinic Acid

Abstract: Maslinic acid is a pentacyclic triterpene extracted from olives that has been systematically reported to exert several therapeutic effects, such as antitumoral, antidiabetic, antioxidant, anti-inflammatory, antiparasitic, and antiviral properties. Recently, new derivatives of maslinic acid have been obtained and expanded the spectrum of biological activities and improved the existing ones. The present study was meant to perform the in vitro assessment of the (i) cytotoxic effects of a benzylamide derivative of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Helium was used as the carrier gas, in a flow rate of 1mL/min. This chromatographer in gas phase was coupled to a mass spectrometry (Hewlett Packard Agilent 5973) with ionization energy of 70 eV, ion source at 230 o C and interface temperature at 280 o C. In vitro antimicrobial activity The determination of antibacterial activity was performed on reference strains (table 1) both by the diffusimetric method on standardized subculture and by the method of dilutions with the MIC (minimum inhibitory concentration) determination, as previously described by other authors [5][6][7][8].…”
Section: Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
“…Helium was used as the carrier gas, in a flow rate of 1mL/min. This chromatographer in gas phase was coupled to a mass spectrometry (Hewlett Packard Agilent 5973) with ionization energy of 70 eV, ion source at 230 o C and interface temperature at 280 o C. In vitro antimicrobial activity The determination of antibacterial activity was performed on reference strains (table 1) both by the diffusimetric method on standardized subculture and by the method of dilutions with the MIC (minimum inhibitory concentration) determination, as previously described by other authors [5][6][7][8].…”
Section: Gas Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
“…The cytotoxicity of compound 1o was tested against MCF‐7 cell‐line (Ali et al, ; Gümüş et al, ; Pavel et al, ; Vichai & Kirtikara, ). The 96‐well microtiter plates containing 100 μL cells in DMEM per well (5.0 × 10 3 cells) were treated after 12 hr with a range of drug concentrations, 0.25, 0.5, 0.78, 1.56, 3.125, 6.25, 12.5 μg/mL, followed by incubation for different time points (24, 48, 72 hr).…”
Section: Resultsmentioning
confidence: 99%
“…Our studies showed the Bcl2-Beclin1 interaction was blocked in the presence of MA, suggesting that the anti-tumor effect of MA probably be exerted through autophagy regulation. Our study reported the molecular mechanism in the biological activities of MA for the first time, providing clue for the researches focused on the development of MA derivatives, aiming to improve the bioactivities of MA [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%